Antimicrobial resistance gene surveillance in the receiving waters of an upgraded wastewater treatment plant - Claire N. Freeman; Lena Scriver; Kara D. Neudorf; Lisbeth Truelstrup Hansen; Rob C. Jamieson; Christopher K. Yost (Canadian Science Publishing, 2018)
Wastewater treatment plants (WWTPs) have been identified as hotspots for antimicrobial resistance genes (ARGs) and thus represent a critical point where patterns in ARG abundances can be monitored prior to their release into the environment. The aim of the current study was to measure the impact of the release of the final treated effluent (FE) on the abundance of ARGs in the receiving water of a recently upgraded WWTP in the Canadian prairies. Sample nutrient content (phosphorous and nitrogen species) was measured as a proxy for WWTP functional performance, and quantitative PCR (qPCR) was used to measure the abundance of eight ARGs, the intI1 gene associated with class I integrons, and the 16S rRNA gene. The genes ermB, sul1, intI1, blaCTX-M, qnrS, and tetO all had higher abundances downstream of the WWTP, consistent with the genes with highest abundance in the FE. These findings are consistent with the increasing evidence suggesting that human activity affects the abundances of ARGs in the environment. Although the degree of risk associated with releasing ARGs into the environment is still unclear, understanding the environmental dimension of this threat will help develop informed management policies to reduce the spread of antibiotic resistance and protect public health.